2023
DOI: 10.1038/s41467-023-36454-8
|View full text |Cite
|
Sign up to set email alerts
|

Intrafusal-fiber LRP4 for muscle spindle formation and maintenance in adult and aged animals

Abstract: Proprioception is sensed by muscle spindles for precise locomotion and body posture. Unlike the neuromuscular junction (NMJ) for muscle contraction which has been well studied, mechanisms of spindle formation are not well understood. Here we show that sensory nerve terminals are disrupted by the mutation of Lrp4, a gene required for NMJ formation; inducible knockout of Lrp4 in adult mice impairs sensory synapses and movement coordination, suggesting that LRP4 is required for spindle formation and maintenance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…Muscle spindles comprise intrafusal fibers sensing muscle length alterations and relay these proprioceptive signals to the brain to coordinate movement, posture, and positional awareness. Cao et al 18 studied the role of low-density lipoprotein receptor-related protein 4 (LRP4) in muscle spindle embryonic and postnatal development and aging. The authors created Lrp4 -Cre ERT2 mice with Ai9 reporter to label cells with an active LRP4 promoter.…”
Section: Muscle Physiology and Regenerationmentioning
confidence: 99%
“…Muscle spindles comprise intrafusal fibers sensing muscle length alterations and relay these proprioceptive signals to the brain to coordinate movement, posture, and positional awareness. Cao et al 18 studied the role of low-density lipoprotein receptor-related protein 4 (LRP4) in muscle spindle embryonic and postnatal development and aging. The authors created Lrp4 -Cre ERT2 mice with Ai9 reporter to label cells with an active LRP4 promoter.…”
Section: Muscle Physiology and Regenerationmentioning
confidence: 99%
“…The APP ectodomain can interact with the ligand binding domain of low-density lipoprotein receptor-related protein 4 (LRP4), thereby inducing the phosphorylation of Musk for AChR clustering on its own or cooperatively with agrin [45] (Figure 3). The LRP4 LDLa domain and APP E1 domain are critical sites for their interaction [46]. The ectodomain of APP can also interact with agrin, although which domain that binds to agrin is not well characterized.…”
Section: App's Binding Partners In Nmjmentioning
confidence: 99%
“…The significance of LRP4 in nervous system function is further highlighted by its association with several human neurodegenerative diseases, including myasthenia gravis (Kalb et al, 2002;Higuchi et al, 2011;Pevzner et al, 2012;Shen et al, 2013;Tsivgoulis et al, 2014;Chung et al, 2023), amyotrophic lateral sclerosis (ALS) (Tzartos et al, 2014) and Alzheimer's disease (Choi et al, 2013;Zhang et al, 2020). In a recent study LRP4 was identified as a novel regulator of muscle spindle formation and maintenance in adult and aged mice (Cao et al, 2023) and LRP4 mediates bone homeostasis and mechanotransduction through interaction with sclerostin (Bullock et al, 2019;Choi and Robling, 2021). In contrast to patients with LRP5-deficiency, who suffer from low bone mass, LRP4 loss-of-function mutations are associated with sclerosteosis 2, characterized by overgrowth of bone mass.…”
mentioning
confidence: 99%